Brief Report: Staged-informed Consent in the Cohort Multiple Randomized Controlled Trial Design. Issue 3 (May 2016) - Young-Afat, Danny A.; Verkooijen, Helena A. M.; van Gils, Carla H.; van der Velden, Joanne M.; Burbach, Johannes P.; Elias, Sjoerd G.; van Delden, Jonannes J.; Relton, Clare; van Vulpen, Marco; van der Graaf, Rieke
Abstract : The "cohort multiple randomized controlled trial, " a new design for pragmatic trials, embeds multiple trials within a cohort. The cohort multiple RCT is an attractive alternative to conventional RCTs in fields where recruitment is slow, multiple new (competing) interventions for the same condition have to be tested, new interventions are highly preferred by patients and doctors, and the risk of disappointment bias, cross-over, and contamination is considerable. To prevent these unwanted effects, the cohort multiple RCT provides information on randomization to the intervention group/arm only, and only after randomization (i.e., prerandomization). To some, especially in a clinical setting, this is not ethically acceptable. In this article, we argue that prerandomization in the cohort multiple randomized controlled trial (cmRCT) can be avoided by adopting a staged-informed consent procedure. In the first stage, at entry into the cohort, all potential participants are asked for their informed consent to participate in a cohort study and broad consent to be either randomly selected to be approached for experimental interventions or to serve as control without further notice during participation in the cohort. In a second stage, at the initiation of an RCT within the cohort, informed consent to receive the intervention is then only sought in those randomly selected for the intervention arm. At the third stage, after completion of each RCT, all cohort participants receive aggregate disclosure of trial results. This staged-informed consent procedure avoids prerandomization in cmRCT and aims to keep participants actively engaged in the research process.